Congenital Co-infections Among HIV-Exposed Infants Born to Mothers on Antiretroviral Treatment in the United States - Christiana Smith; Lori Silveira; Megan Crotteau; Krystle Garth; Jennifer Canniff; Kirk B. Fetters; Sarah Lazarus; Shannon Capraro; Adriana Weinberg; Adriana Weinberg; the CHIP Perinatal Team (Frontiers Media S.A., 2022)
BackgroundMany women living with HIV (WLHIV) are co-infected with cytomegalovirus (CMV), Toxoplasma gondii (T gondii), and/or hepatitis C virus (HCV). The rates of congenital or perinatal transmission of these co-infections are not well defined in the current era, when most WLHIV receive antiretroviral therapy (ART) during pregnancy.MethodsRetrospective review of infants of WLHIV born between 2009-2019. Mothers were screened for antibodies to CMV, T. gondii, and HCV; chronic HCV infection was confirmed using plasma RNA PCR. Infants whose mothers had positive/unknown serostatus were screened for CMV using urine or saliva DNA PCR or culture at ≤3 weeks of life; T. gondii using serology at ≤1 month; and HCV using plasma RNA PCR at ≤6 months and serology at ≥12 months.ResultsThe study included 264 infants from 255 pregnancies in 191 mothers. At delivery, the median (IQR) CD4 count was 569 (406-748) cells/mm3 and plasma HIV load was 0 (0-24) RNA copies/mL. Among 243 infants born to CMV-seropositive (209) or CMV-missed serostatus (25) mothers, 163 (67.1%) were tested for CMV. Four infants had CMV detected, resulting in a rate of congenital infection of 2.5%. Among 65 infants from 54 (21.2%) pregnancies in T. gondii-seropositive women and 8 in women with unknown T. gondii-serostatus, one acquired congenital toxoplasmosis in the setting of acute maternal T. gondii infection. There were no episodes of vertical transmission from mothers with latent toxoplasmosis. Among 18 infants from 13 (5.1%) pregnancies in HCV RNA PCR-positive women and 4 in women with unknown HCV serostatus, there were no congenital or perinatal HCV transmissions.ConclusionsIn a US cohort of pregnant WLHIV on ART, we identified high maternal CMV seroprevalence and a high rate of congenital CMV infection. We did not identify any congenital or perinatal transmissions of T. gondii or HCV among mothers who had latent or chronic infections. Our data support screening pregnant WLHIV and their infants for CMV and suggest that the rates of congenital and perinatal T. gondii and HCV infections among infants born to WLHIV on ART may be lower in the era of effective ART.